Tour around the globe: The case of invasive tapeworm Atractolytocestus huronensis (Cestoda: Caryophyllidea), a parasite of common carp - Bazsalovicsová, Eva; Králová-Hromadová, Ivica; Xi, Bing-Wen; Štefka, Jan (Parasitology international, 2018)
The monozoic tapeworm Atractolytocestus huronensis Anthony, 1958 (Cestoda: Caryophyllidea), an intestinal parasite of the common carp, is characterized by its invasive character and potential to colonize new territories. It was initially described from North America and has also been found in several European countries. The most recent findings of A. huronensis originated from China and South Africa; however, no data on genetic relationships of these populations were available. The current study provides the first molecular characterisation of A. huronensis from South Africa and China using a partial sequence of mitochondrial cytochrome c oxidase subunit 1 (cox1) and a complete ribosomal ITS2 spacer. Ribosomal and mitochondrial data were applied for phylogenetic analyses in order to assess the genetic interrelationships among global A. huronensis populations. Divergent intragenomic copies of ribosomal ITS2 were detected in all analysed specimens; the structure and frequency of the ITS2 variants of tapeworms from China and South Africa corresponded with the data on ITS2 paralogues observed previously in A. huronensis from Slovakia, the United States and the United Kingdom. The phylogenetic analysis of cox1 indicated that A. huronensis exist in two slightly differentiated clusters; one cluster was supported by all phylogenetic approaches (NJ, ML, BI) and was represented by samples from China, the USA and the UK. A second cluster was represented by tapeworms from continental Europe (Slovakia, Hungary, Romania, Croatia) and South Africa. Haplotype network analysis revealed that the highest population diversity occurs in China. The results provide useful pilot information about the interrelationships of A. huronensis on four continents and indicate that China, or the eastern Palaearctic, served as the original source population for the global expansion of this invasive tapeworm. Data on the origin and distribution of the common carp, the only specific host of A. huronensis, are also discussed.
Keywords: Animals; Rumunsko; Romania; Intestines; United Kingdom; Europe; Electron Transport Complex IV; Cestoda; China; kapři; cestodózy; nemoci ryb; respirační komplex IV; Evropa; Fish Diseases; Spojené království; mezerníky ribozomální DNA; DNA, Helminth; Phylogeny; střeva; DNA helmintů; Croatia; zavlečené druhy; Chorvatsko; Čína; Carps; DNA, Ribosomal Spacer; Cestode Infections; zvířata; fylogeneze; Introduced Species